ANALISIS USAHATANI DAN PEMASARAN JAMUR TIRAM DENGAN CARA KONVENSIONAL DAN JARINGAN (MULTI LEVEL MARKETING) DI PROVINSI LAMPUNG - Reki Candra; Dyah Aring Hepiana L; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This research aims to analyze: whether the oyster mushroom farm in Lampung Province profitable or not, and the efficiency of oyster mushroom marketing system in a conventional manner and the network inLampung Province. The research was conducted in Lampung Province especially in Bandar Lampung and Metro City. The research location was chosen on purpose. The farmer respondents were chosen by censusand the imtermediatory marketing institution was taken by following the marketing’s flow. The data was collected in January-August 2013. The research results showed that oyster mushroom farming in LampungProvince was profitable for oyster mushroom farmers in which R/C ratio of the cash costs was 1.95 and R/C ratio of the total cost was 1.29. The efficiency of oyster mushroom marketing were as follows: (a) market structure formed in conventional manner was oligopsony, while the network marketing was oligopoly; (b) market behavior: oyster mushroom farmers, both conventional and network marketing sold their crops and be paid in cash. (c) Marketing oyster mushroom by forming a group of network marketing upline and downline network had relatively much benefit than the conventional one.Keywords: conventional marketing, network marketing, oyster mushroom